2015
DOI: 10.1371/journal.pone.0125623
|View full text |Cite
|
Sign up to set email alerts
|

IL17 Mediates Pelvic Pain in Experimental Autoimmune Prostatitis (EAP)

Abstract: Chronic pelvic pain syndrome (CPPS) is the most common form of prostatitis, accounting for 90–95% of all diagnoses. It is a complex multi-symptom syndrome with unknown etiology and limited effective treatments. Previous investigations highlight roles for inflammatory mediators in disease progression by correlating levels of cytokines and chemokines with patient reported symptom scores. It is hypothesized that alteration of adaptive immune mechanisms results in autoimmunity and subsequent development of pain. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 62 publications
4
46
1
3
Order By: Relevance
“…The effect of NPI instillation on prostatic immune responses was examined by flow cytometric analysis of CD4+ve T-cells. Increased levels of CD4+ve IL17A+ve T-cells were observed upon induction of EAP in prostate tissues, (Figure 2c), as previously reported [25], and this increase was lost upon treatment with NPI for 7 days. We also observed a reversal of increased IL17A expressing CD4 T-cells in the iliac lymph nodes (Figure 2d) of EAP mice following NPI instillation, where levels returned to those similar to naïve mice.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The effect of NPI instillation on prostatic immune responses was examined by flow cytometric analysis of CD4+ve T-cells. Increased levels of CD4+ve IL17A+ve T-cells were observed upon induction of EAP in prostate tissues, (Figure 2c), as previously reported [25], and this increase was lost upon treatment with NPI for 7 days. We also observed a reversal of increased IL17A expressing CD4 T-cells in the iliac lymph nodes (Figure 2d) of EAP mice following NPI instillation, where levels returned to those similar to naïve mice.…”
Section: Resultssupporting
confidence: 86%
“…Increases in CD4+ve T-cell derived IL17A is necessary for initiation of pelvic tactile allodynia in the EAP murine model [32; 39]. Analysis of human EPS samples demonstrated that IL7, a cytokine involved in maintenance of activated CD4 T-cells [25], is increased in CPPS patients and correlated with pain severity. These lines of evidence suggest that the interplay between bacteria and the local immune system may have specific roles in determining referred alloydnia.…”
Section: Introductionmentioning
confidence: 99%
“…Moseley and coworkers indicated that in current versions of the EST database some isoforms of IL-17 are expressed in the prostate [21]. Other authors also demonstrated by immunohistochemistry that IL-17 increases its expression in both stromal and epithelial tissue of the dorsolateral prostate in a murine prostatitis model [22]. In our case we observed in normal group an IL-17 signal in basal and luminal glandular regions (Figure 4(a)).…”
Section: Resultssupporting
confidence: 65%
“…Previous publications from our laboratory have demonstrated that EAP induced immune activation in prostate tissues is mediated by adaptive T-cell immune responses, specifically Th17 cells. 21 We hypothesized that PAR2 may mediate maintenance of inflammatory signals via mast cells and in doing so contribute to fibrosis. To address this we performed flow cytometry for a number of adaptive and innate immune cell markers at 5 and 30 days post-EAP induction in PAR2 KO mice.…”
Section: Discussionmentioning
confidence: 99%